you are correct, it is one to two
<h3>
Answer: 14.85 + c = 20</h3>
============================================================
Reason:
To compute the change, we subtract the amount William gives the cashier (the $20) and the price of the book ($14.85)
The change c is
c = 20-14.85
To rearrange this equation, we can add 14.85 to both sides to end up with 14.85 + c = 20
In other words, solving that equation in bold leads to c = 20-14.85 = 5.15 which is the change William is given.
----------------
Extra info (optional section)
If the cashier wanted to mentally figure out the change in his/her head, then notice the jump from 85 cents to 100 cents is 15 cents. That means we go from 14.85 to 15.00
Then the jump from $15 to $20 is an extra 5 dollars. Overall, the total change given back to William is 0.15+5 = 5.15 dollars.
Answer:
yes, by AAS there are two sides of corresponding angles
Step-by-step explanation:
HOPE this helps...
Answer:
(3) y=(x+3)
Step-by-step explanation:
I'm not sure what is the parent function, but in most graphs if you will shift it to the left or right (negative sign or positive sign, respectively), it will be inside a parenthesis and the opposite sign is the real movement.
For a cubic function these will be the movements:
f(x)=(x+/-h)^3+/-k
Only the opposite sign of h will be the real movement, while k's sign will automatically indicate the correct movement.
h= x-axis movement (horizontal, inside of the parenthesis in the equation)
k= y-axis movement (vertical, outside of the parenthesis in the equation)
Hope it helps
The average rates of change of f(x) and their corresponding intervals are given as:
Interval Rate of Change
[-5, -1] -8
[-4, -1] -7
[-3, 1] -4
[-2, 1] -3.
<h3>What is the explanation for the above?
</h3>
Step 1 - See Table Attached
Step 2 - State the formula for rate of change
The formula for rate of change is given as:
= [change in f(x)] / [change in x]
a) For interval [5, -1] ⇒
Rate of Change - [ f(1) - f(-5) ] / [-1 - (-5)]
= [-1 - 35] / [-1+5]
= -36 / 4
= - 8
b) For interval [-4, -1] ⇒
rate of change = [ f(-1) - f(-4) ] / [ -1 - (-4) ]
= [3 - 24] / [-1 + 4]
= -21/3
= - 7
c) interval [-3,1] ⇒
rate of change = [ f(1) - f(-3) ] / [ 1 - (-3) ]
= [-1 - 15] / [1 + 3]
= -16/4
= - 4
d) interval [-2,1] ⇒
rate of change = [f (1) - f(-2)] / [1 - (-2)]
= [ -1 - 8] / [1 + 2]
= -9/3
= -3
Learn more about rate of change at:
brainly.com/question/25184007
#SPJ1